COMPARISON OF THE WHO FORMULA A AND B HANDRUB EFFECTIVENESS AGAINST Staphylococcus aureus : STUDY IN DIPONEGORO NATIONAL HOSPITAL EMERGENCY ROOM, HIGH CARE UNIT, AND STOREROOM BASED ON prEN12054 MODIFICATION - Daniel, Yohanes; Lestari, Endang Sri; Ciptaningtyas, V. Rizke (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2018)
Introduction: Good implementation of hand hygiene and the availability of cheap, affordable, and effective hand rub can prevent healthcare-associated infection. WHO has issued hand rub formulations that are easily self-produced, effective, and affordable. Objective: This study compares the difference between handrub’s effectiveness stored in National Hospital Diponegoro University ER, HCU, and storeroom for 2 and 10 weeks.Methods: This study was an experimental study with pretest posttest randomized group design. The effectiveness of hand rub measured by prEN12054 in cfu/ml. Results: There was no significant difference between efficacy of WHO formula A and B (p=0.458). In the Mann-Whitney test there was no difference between the effectiveness of WHO A and B formulas before storage (p = 0.567), after being stored for two weeks (p=1.000), and ten weeks (p=0.539). In the Kruskal-Wallis test, there was no difference in the effectiveness of the WHO A formula in three sites at weeks 0, 2 and 10 (p = 0.275, 0.584, 0.116), there was no difference in the effectiveness of the WHO B formula in three sites at week 0, the 2nd and 10th (p = 0.289.; p = 0.584, p = 1.000).Conclusion: No significant differences were found on the effectiveness of the WHO A and B formulas. There was no significant difference in the effectiveness of WHO A or B formulas stored in three sites. There were no significant differences in the effectiveness of WHO A or B formulas, before and after being stored for two and ten weeks in three sites.